Brecht, Hegel, Lacan: Brecht's Theory of Gest and the Problem of the Subject - Philip E. Bishop (Studies in 20th & 21st Century Literature, 1986)
Brecht used the term "gest" to describe the generic components of human social behavior. He schooled actors in "decomposing" real conduct into distinct gestic images, which were criticized, compared, and altered by other actor-spectators. In his pedagogic theater, Brecht's young players engaged in a reciprocal process of acting and observing, which prepared them to act critically outside the theater. This gestic reciprocality echoes the master-slave dialectic in Hegel's Phenomenology and Lacan's description of the mirror phase. In Hegel, a subject achieves mastery (or self-consciousness) through the recognition of another subject. In Lacan, the infant recognizes itself in an (alienated) mirror-image and in its dramatic interactions with other infants. In each of these inter-subjective dialectics, the subject achieves sovereignty through the recognition of others and through a dramatic exchange with others. For Brecht, however, the structural roles of actor and spectator, teacher and student, were reversible, thus yielding a utopian notion of shared or collective sovereignty that is absent from Lacan. Furthermore, Brecht hoped that the sovereignty gained in the gestic theater would be transferred to actions outside the theater, on the stage of history.
Keywords: Brecht; Hegel; Lachan; gest; human social behavior; decomposing; gestic images; actor; spectators; pedagogic theater; observing; acting; Phenomenology; mirror stage; alienated; recognition; utopian; utopia; gestic theater; theater; stage